REGIONAL CLEAVAGES OF THE ELECTORAL FIELD OF UKRAINE AND THEIR IMPACT ON THE CONFIGURATION OF THE PARTY SYSTEM IN 1990–2014 - Гудзь, Віталій (SWorldJournal, 2025)
The author has studied the features of regional cleavages in Ukraine, which affect the electoral preferences of the population of the regions and the configuration of the party system. The study of electoral cycles and the results of parliamentary electio